2009
DOI: 10.1177/112070000901900308
|View full text |Cite
|
Sign up to set email alerts
|

Resurfacing and Uncemented Arthroplasty for Young Hip Arthritis: Functional Outcomes at 5 Years

Abstract: The management of osteoarthritis of the hip in young active patients is challenging. We compared the functional outcomes and activity levels following hip resurfacing and uncemented THA in young active patients matched for age, gender and activity levels. Mean follow-up period was five years (4-7 years). Within each group there was a statistically significant improvement in the mean University of California at Los Angeles (UCLA) and Oxford Hip Score (OHS) scores following surgery. This study found no statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Our assessment of generic QoL (SF-12) demonstrated improvements on the physical and mental component scores comparable to the nonarthritic population. These outcomes support and underscore recent reports on WOMAC scores [25,38,39,41,57,59,69,70] and Oxford Hip Scores [31,36,[56][57][58] from other authors and patient populations. Our SF-12 results are in agreement with published SF-12 and SF-36 outcomes, which demonstrate restoration of generic QoL approaching that of the normal population [16,41,56,58] (Table 4).…”
Section: Resultssupporting
confidence: 70%
“…Our assessment of generic QoL (SF-12) demonstrated improvements on the physical and mental component scores comparable to the nonarthritic population. These outcomes support and underscore recent reports on WOMAC scores [25,38,39,41,57,59,69,70] and Oxford Hip Scores [31,36,[56][57][58] from other authors and patient populations. Our SF-12 results are in agreement with published SF-12 and SF-36 outcomes, which demonstrate restoration of generic QoL approaching that of the normal population [16,41,56,58] (Table 4).…”
Section: Resultssupporting
confidence: 70%
“…However, Marker et al [35] reported similar functional hip scores and radiographic assessment in a recent review of the literature comparing hip resurfacing with THA, although a number of studies included in the review did show better clinical outcomes after hip resurfacing [35]. In addition to this, Killampalli et al [27] reported no differences in functional scores in young patients treated with hip resurfacing compared with THA at a minimum 5-year followup. Despite this, hip resurfacing as an alternative to conventional THA does offer a number of advantages: preservation of the metaphyseal and diaphyseal femoral bone; improved radiographic biomechanical parameters of the hip e.g.…”
Section: Introductionmentioning
confidence: 86%
“…Hip resurfacing remains a successful implant in relatively young males with normal anatomy, but in other patient groups popularity with surgeons has reduced dramatically. Even in the young male group there is no demonstrable superiority in terms of function or longevity when compared to traditional hip replacements [128]. Other conservative hip replacements are in development, but at this stage must be regarded as experimental.…”
Section: Hip Resurfacingmentioning
confidence: 98%